Characteristics of management subjects of personalized development of management personnel of educational organization - V. V. Tarasenko (Управление)
The results of the ongoing study of the system of personalized development of administrative personnel of the educational organization have been presented. The purpose of the study was to determine the composition and functions of the subjects of management of personalized development of administrative personnel of the educational organization, acting as a necessary element of the system under study. The research has solved the following tasks: the essence of personalized development of administrative personnel of the educational organization has been clarified; the composition of constituent entities manage personal development of managerial staff of the educational institution has been determined; the functions of subjects of management personal development management personnel of the educational organization have been revealed.The essence of personalized management personnel development educational organizations as a process of realization of set organizational and economic measures irreversible, directed and natural qualitative change of an object state development - updating of its competencies, necessary for effective implementation of social roles and functions of the administrative personnel of the educational organization in accordance with personalized requirements and needs of key stakeholders in this process, has been substantiated.The main structure of subjects of management of personalized development of administrative personnel of an educational organization has been presented, which includes: personnel of an educational organization as an object of development and subject of self-development, educational organizations with the need for development of administrative personnel, regional and municipal methodological services, organizations of higher and additional professional education. In conclusion, a meaningful characteristic of the functions of the subjects of management personalized development of management personnel of the educational organization has been provided.In the process of solving the problems of the study, the following methods were used: structural and functional analysis of the domestic education system; analysis of the legal and organizational and methodological support of the activities of the subjects of development of administrative personnel of educational organizations; monitoring of participants in educational relations.